Smart-Phone Assisted Language Learning in a Public University in Saudi Arabia - Karem Abdelatif Mohamed; Tanzina Halim (Universitas Negeri Makassar, 2023)
The present study tried to investigate EFL teachers' and learners’ facilities regarding smartphone-assisted language learning (SALL) in the Faculty of Languages and Translation, King Khalid University (KKU), Saudi Arabia, including their attitudes, perceptions, levels of proficiency, and challenges they experienced. The study also pursued to inspect whether EFL teachers’ experiences have any significant influence on their facility of SALL. Investigation data was composed of (45) EFL teachers and (68) EFL learners. Two questionnaires were used to collect data. Some statistical analyses were used. The results showed EFL teachers' and learners’ positive perceptions of SALL. Participants stated that (SALL) is beneficial and has supported and enhanced EFL teaching and learning. Most EFL teachers said they needed more skills to advance SALL activities and mentioned some challenges they confronted. The results also indicated significant differences among participants’ SALL facility based on their professional development and teaching experiences, but no differences based on their gender were found. These results also showed that emphasizing professional development in SALL for KKU EFL teachers could promote greater proficiency and the facility to overcome challenges. The study concluded by providing recommendations on advancing SALL implications and suggestions. Keywords: EFL Learners, EFL Teachers, Facility, Implication, Smartphones